Equity–efficiency optimizing resource allocation: The role of time preferences in a repeated irrigation game - Van Campenhout, Bjorn; D'Exelle, Ben; Lecoutere, Els (Wiley, 2015)
We study repeated water allocation decisions among small scale irrigation users in Tanzania. In a treatment replicating water scarcity conditions, convexities in production make that substantial efficiency gains can be obtained by deviating from equal sharing, leading to an equity–efficiency trade-off. In a repeated game setting, it becomes possible to reconcile efficiency with equity by rotating the person who receives the largest share, but such a strategy requires a longer run perspective. Correlating experimental data from an irrigation game with individual time preference data, we find that less patient irrigators are less likely to use a rotation strategy.